Intravital imaging of translocated bacteria via fluorogenic labeling of gut microbiota in situ - Xinqi Fan; Yingjun Zhou; Wenjuan Bai; Xue Li; Liyuan Lin; Huibin Lin; Ming Yang; Xiaofei Yu; Jing Wang; Liang Lin; Wei Wang (Proceedings of the National Academy of Sciences, 2025)
The translocation of bacteria from intestinal tracts into blood vessels and distal organs plays pivotal roles in the pathogenesis of numerous severe diseases. Intravital monitoring of bacterial translocation, however, is not yet feasible, which greatly hinders us from comprehending this spatially and temporally dynamic process. Here we report an in vivo fluorogenic labeling method, which enables in situ imaging of mouse gut microbiota and real-time tracking of the translocated bacteria. By mimicking the peptidoglycan stem peptide in bacteria, a tetrapeptide probe composed of alternating D- and L-amino acids and separately equipped with a fluorophore and a quencher on the N- and C-terminal amino acid, is designed. Because of its resistance to host proteases, it can be directly used in gavage and achieves fluorogenic labeling of the microbiota in the gut via the functioning of the L,D-transpeptidases of the labeled bacteria. Using intravital two-photon microscopy, we then successfully visualize the translocation of gut bacteria into the bloodstream and liver in obesity mouse models. This technique can help further exploration into the spatiotemporal activities of gut microbiota in vivo, and be valuable in investigating the less understood pathogenicity of bacterial translocation in many severe diseases.